That summer : a novel - Weiner, Jennifer (Atria Books, 2021)
While trying to pinpoint the root of her dissatisfaction with her life, Daisy Shoemaker begins receiving misdirected emails meant for another woman and starts living vicariously through her until she discovers that their connection was not completely accidental.